UV Mutagenesis as a Strategy to Enhance Growth and Lipid Productivity of Chlorella sp. 042 - Rike Rachmayati; Eva Agustriana; Delicia Yunita Rahman (Universitas Gadjah Mada, 2020)
Microalgae appeared to be an alternative feedstock for renewable biodiesel production due to their capability to accumulate considerable amounts of lipids. In this study, mutagenesis using UVC light with different periods was applied to Chlorella sp. 042 to produce a microalgae strain with high lipid productivity of 45, 60, and 75 min. The Nile red fluorescence method was conducted to select a Chlorella sp. mutant with high neutral lipid and generated one mutant from every UV mutation period, M45-06, M60-02, and M75-21. All of the mutants have higher growth rates than the wild type. Chlorella sp. 042 M60-02 achieved the highest lipid productivity, with 34 mg L-1 day-1. Furthermore, as other major biochemical components, carbohydrate and protein contents were determined. Our results showed that all the mutants enhance their carbohydrate and protein contents compared to the wild type. However, mutations for more than 60 min do not intensely change the protein content of mutant microalgae. Gas chromatography-mass spectrophotometry analysis revealed that M60-02 mutant has similar FAME profiles with the wild type, which contain palmitic acid (C16:0), stearic acid (C 18:0), oleic acid (C18:1), and linoleic acid (C18:2). These results demonstrate that the UV mutation of Chlorella sp. 042 for 60 min is suitable as a source of biodiesel production.